Syntheses and applications of C-2-symmetric chiral diols - Bhowmick, Kartick C.; Joshi, Navalkishore N. (Tetrahedron-Asymmetry, 2006)
Synthetic procedures for a large variety of C-2-symmetric chiral diols are reviewed. Prominent among these procedures are enantioselective reductions, epoxide-cleavages, dihydroxylation of olefins, and synthetic transformations. Applications of these diols as chiral auxiliaries/ligands for several important reactions are also highlighted. (c) 2006 Elsevier Ltd. All rights reserved.